Migration-linked TB epidemics: How TB elimination in high-income countries depends on the success of TB control in high-burden settings - Byron L. M. Cohen; Kevin Croke; William P. Hanage; Ted Cohen; Nicolas A. Menzies (Proceedings of the National Academy of Sciences, 2026)
Mycobacterium tuberculosis is the leading global cause of infectious disease deaths. A growing proportion of tuberculosis cases in high-income countries occur among foreign-born individuals, due to infections acquired before migration. We developed a system of mathematical models representing tuberculosis epidemiology in 187 countries, linked by migration patterns, and trained on empirical data for each setting. Using these models, we quantified how future tuberculosis risks in high-income countries are influenced by the success or failure of efforts to combat tuberculosis in high-burden settings. Over 2025–2050, we projected 2270,000 (95%CI: 1930,000 to 2730,000) tuberculosis cases in high-income countries if pre-2025 trends continue, with 54% (46 to 62) among foreign-born individuals (versus 39% in 2024), for an average incidence of 6.0 (4.8 to 7.7) per 100,000 in 2050. Under the most optimistic scenario (assuming high-burden countries achieve aggressive WHO tuberculosis elimination targets), we estimated 667,000 (559,000 to 812,000) fewer tuberculosis cases in high-income countries over 2025–2050, with incidence of 2.6 (2.1 to 3.3) per 100,000 in 2050. Under the most pessimistic scenario (reduced international health aid causes rising tuberculosis in high-burden countries), we estimated 890,000 (793,000 to 998,000) additional tuberculosis cases in high-income countries, with incidence of 10.2 (8.4 to 12.7) per 100,000 in 2050. The United States, United Kingdom, Germany, Singapore, and France were the most affected high-income countries. For high-income countries, future tuberculosis incidence and mortality could vary by as much as 4 times depending on the success or failure of tuberculosis control in high-burden settings, fundamentally shaping strategies to prevent, detect, and treat tuberculosis in these settings.